2019
DOI: 10.1038/s41467-019-10959-7
|View full text |Cite
|
Sign up to set email alerts
|

Strength of carbon nanotubes depends on their chemical structures

Abstract: Single-walled carbon nanotubes theoretically possess ultimate intrinsic tensile strengths in the 100–200 GPa range, among the highest in existing materials. However, all of the experimentally reported values are considerably lower and exhibit a considerable degree of scatter, with the lack of structural information inhibiting constraints on their associated mechanisms. Here, we report the first experimental measurements of the ultimate tensile strengths of individual structure-defined, single-walled carbon nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(97 citation statements)
references
References 37 publications
2
95
0
Order By: Relevance
“…The history of nanotubes [1,2] and fullerenes [3] spans several decades; the most important stages in understanding of their nature and properties are well represented in recent reviews and books [4][5][6][7][8][9][10]. The main directions of practical application of such nanoobjects are connected with creation of new materials [4,[7][8][9][10][11][12][13][14], applications in pharmacy and medicine [15][16][17][18][19][20][21][22][23][24] and wastewater treatment [25]. These possibilities resulted mainly from the formation of endohedral complexes of fullerenes and nanotubes; the first example, synthesis of lanthanum complexes of C 60 , was described in [26].…”
Section: Introductionmentioning
confidence: 99%
“…The history of nanotubes [1,2] and fullerenes [3] spans several decades; the most important stages in understanding of their nature and properties are well represented in recent reviews and books [4][5][6][7][8][9][10]. The main directions of practical application of such nanoobjects are connected with creation of new materials [4,[7][8][9][10][11][12][13][14], applications in pharmacy and medicine [15][16][17][18][19][20][21][22][23][24] and wastewater treatment [25]. These possibilities resulted mainly from the formation of endohedral complexes of fullerenes and nanotubes; the first example, synthesis of lanthanum complexes of C 60 , was described in [26].…”
Section: Introductionmentioning
confidence: 99%
“…Studies concerning carbon nanotubes (CNT) have surged since the groundbreaking work reported by Iijima 19 . The tensile strength of individual CNT can reach as high as 66 GPa 20 which is two orders of magnitude higher than that of steel. In addition, the electrical conductivity of CNTs ranges from 8 × 10 −6 to 20 × 10 −6 Ω m as per Dai et al 21 and the thermal conductivity of CNT falls in a range of 2000 ~ 6000 W/mK as per Han and Fina 22 .…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, SPCs can exhibit exotic adsorption properties with application in the area of gas storage, separation and sensing. [17][18][19][20][21][22][23][24][25][26] Despite extensive knowledge about the mechanical properties of polymers and metals typically used in the construction of macroscopic metamaterials and the advancing understanding of the mechanical properties of nanoscopic materials such as poly(ethylene glycol), 27 DNA, 28 or carbon nanotubes, 29 little is known regarding the mechanical behaviour of individual small molecules and their influence on the elastic and inelastic response of molecular crystalline frameworks. 30,31 In 2016, we discovered the counterintuitive adsorption phenomenon termed negative gas adsorption (NGA) in the flexible MOF named DUT-49 (Dresden University of Technology Nr.…”
Section: Introductionmentioning
confidence: 99%